Seguimiento del alga Rugulopteryx okamurae en la costa del mar de Alborán. - Ferres García, José Luis; Bañares-España, Elena; Celis Plá, Paula; Avilés-Benítez, Antonio; Bermejo-Lacida, Ricardo; Moreu Badia, Ignacio; Núñez, África; López-Figueroa, Félix; Korbee-Peinado, Nathalie (My University, 2023)
Rugulopteryx okamurae is a macroalgae native to the Pacific Ocean, which has established itself on the northern and southern coasts of the Alborán Sea, becoming a serious problem due to its rapid growth, being included in the list of invasive species in Spain in 2020. The main problems are related to loss of biodiversity, as well as loss of money in fishing and tourism. BLUEMARO project focuses on the monitoring of the brown algae R. okamurae along the Andalusian coastline. The main objective is to increase the knowledge about this species, its ecologic strategies of adaptation to the environment to try to predict its continuous expansion. Within the project, there are different branches of study (oceanographic, ecophysiology, biotechnological), and here, we will focus on the benthic studies of the algae, as well as the chemical and photobiological analysis of the compounds present in it. These marine studies have been carried out during the different seasons of the year 2022-2023, in three different locations (Maro, Estepona and Tarifa). In each of these samplings, we monitored the cover of R. okamurae and other species in different transects. Likewise, specimens of R. okamurae were collected for subsequent analysis in the laboratory, to establish the existence of differences between the different settled populations, as well as their variability throughout the year. Preliminary sampling results show differences for the populations studied, and seasonal changes for the same location. Likewise, biochemical, and photosynthetic preliminary results show differences in the same terms.
Keywords: Algas marinas; Especies exóticas invasoras; Alborán; Mediterraneo; Alga; Rugulopteryx; Okamurae; Ecología; Posidonia; Oceanografía